Are the observed gaps in protoplanetary discs caused by growing planets? - Ndugu, N.; Bitsch, B.; . Jurua, E (Oxford University Press on behalf of the Royal Astronomical Society, 2019)
ABSTRACT Recent detailed observations of protoplanetary discs revealed a lot of substructures that are mostly ring like. One interpretation is that these rings are caused by growing planets. These potential planets are not yet opening very deep gaps in their discs. These planets instead form small gaps in the discs to generate small pressure bumps exterior to their orbits that stop the inflow of the largest dust particles. In the pebble accretion paradigm, this planetary mass corresponds to the pebble isolation mass, where pebble accretion stops and efficient gas accretion starts. We perform planet population synthesis via pebble and gas accretion including type-I and type-II migration. In the first stage of our simulations, we investigate the conditions necessary for planets to reach the pebble isolation mass and compare their position to the observed gaps. We find that in order to match the gap structures 2000ME in pebbles is needed, which would be only available for the most metal-rich stars. We then follow the evolution of these planets for a few Myr to compare the resulting population with the observed exoplanet populations. Planet formation in discs with these large amounts of pebbles results in mostly forming gas giants and only very little super-Earths, contradicting observations. This leads to the conclusions that either (i) the observed discs are exceptions, (ii) not all gaps in observed discs are caused by planets, or (iii) that we miss some important ingredients in planet formation related to gas accretion and/or planet migration.
Keywords: Accretion; Accretion Discs; Hydrodynamics; Planet; Disc Interactions